Implementation of Sustainable Development Goals (SDGs) in Tourism Management in Pemuteran Tourism Village - Putra, Pande Gifta Yudhistira; Dianasari, Dewa Ayu Lily; Sukariyanto, I Gede Made; Liestiandre, Hanugerah Kristiono (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study evaluates the implementation of SDGs in tourism management in Pemuteran Tourism Village which focuses on all SDGs points (18 SDGs). Using a qualitative approach with interviews, observations, documentation and literature studies. This study found that Pemuteran Tourism Village has generally succeeded in implementing SDGs. This is reflected in sustainable tourism practices that create jobs, increase environmental awareness through environmental programs and activities, and maintain a balance between modern social life and local wisdom. However, Pemuteran Village still needs to increase efforts in meeting several SDGs indicators that have not been implemented, such as natural resource protection policies and more effective environmental management.